Pengaruh Penggunaan Media Permainan Ular Tangga Kimia Materi Koloid terhadap Hasil Belajar Peserta Didik Kelas XI MAN 1 Padang Lawas - Nivelda Yani Hasibuan; Iswendi Iswendi (Universitas Negeri Padang, 2021)
ABSTRACT The availability of the chemistry game of snakes and ladders that have tested for validity, practicality and effectiveness, but has not tested for their effect on student achievement in the cognitive domain. The purpose this study to determine the effect of using the chemistry game of snakes and ladders on colloid material on students’ achievement of MAN 1 Padang Lawas. This type of research is a quasi- research and the research design is Randomized Control Group Posttest Only Design. The population of this study all students of class. Sampling used the Simple Random Sampling technique, so that the XI MIA 1 class was obtained as the experimental class and the XI MIA 3 class as the control class. From this assessment, the results of the posttest obtained with an average value of 82.2 for the experimental class and 78.8 for the control class. Data analysis was performed by t-test at a significance level of 0.05. The results of the analysis obtained tcount = 4.438 and ttable = 1.665. Because tcount > ttabel means H0 is rejected and H1 is accepted. It can be said that there is a significant effect of using colloid chemistry game media on the achievement in class XI MAN 1 Padang Lawas. keywords, influence, chemstry snake and ladders game, colloid, students’ achievement